ANALISIS PRODUKTIVITAS PADI SAWAH DI KUPANG TIMU& NUSA TENGGARA TIMUR (RICE FIETDS PRODUCTIVITY ANALISIS IN KUPANG TIMUR, EAST NUSA TENGGARA) - Taufik, Mohamad; Raliman, Raliman; Hermawan, R. (Jurnal Ilmu-Ilmu Pertanian, 2011)
This research aimed to study rice field productivity in Kupang Timur, NTT. The research was carried out on April 30th 20ll in East Kupang District. Data analysis used in the research was Magic Box method. The principle use of the magic box was by using parameters of productivity and stability. The research used paddy fields productivity data in the villages of Oefafi, Pukdale, Nunkurus, Manusak, Oesao, Oelatimo, and Tanah Putih; and the villages of Tuatuka, Oesao, Babau, and Merdeka, during 2006-2010. In the research, paddy field productivity was considered as low if: productivity <29.8kw/ha; moderate if:29.8< the Productivity< 49.6kw / ha; and high if: productivity ≥ 49,6 kw/ha. Stability was categorized as low if the Coefficient of Variation (CV): CV> 20%,; moderate if: CV 10-20%; and high if CV< 10%. Results of analysis showed that the magic box outcome for Oefafi Village, Pukdale, Ninkurur, Manusak, and Oelatimo; and Village Tuatuka, Oesao, Naibonat, Babau, and Merdeka had the same stability and productivity levels, i.e. medium productivity and high stability (Box 4), while the village oesao andTanah Putihproductivity and stability were medium (Box 5). ' According to the outcome of the magic box, farmer group empowerment efforts should be done through two approaches, namely , research and extension. Farmer group empowerment include the following activities: 1) The use of improved labelled seed, 2) fostering group labelled breeder seed, 3) utilization of livestock wastes for organic fertilizer production; 4) Structuring the cropping pattern and crop plots;-5) Improved post-harvest activities; 6) Optimization of the land cultivation; 7) Optimization of pest control with IPM principles, and Group coaching'